76 Foundation doctors as leaders of first aid teaching and health promotion in UK secondary schools through #HealthinSchools: a national programme endorsed by the UKFPO. (3rd November 2019) - Soltan, Marina; Sapey, Liz; Melville, Colin; Choules, Tony; MacEwen, Carrie; Nightingale, Peter; Thickett, David; Hamel, Clare van; Young, Tony
Abstract : Background: The present study, #HealthinSchools, explores health professionals in training as leaders of first aid teaching and health promotion in UK secondary schools. First aid teaching in schools is associated with improved cardiac arrest outcomes and was mandated by the UK government in January 2019. Diet, sleep hygiene, smoking cessation, alcohol moderation and 20 minutes of daily exercise have been shown to prevent cardio-respiratory disease and alleviate depression. Aims: This study aims to: A) Identify an evidence-based approach to lead first aid teaching in UK schools, B) Promote behaviour change to prevent modifiable risk factors and co-morbidities, C) Up-skill foundation doctors with leadership skills, D) Drive a sustainable NHS workforce which represents the community it serves. Methods: First aid teaching was delivered by 51 foundation doctors to 3251 UK secondary school children in 17 schools in regions of varying deprivation. Teaching sessions lasted one hour and were structured to include an: introduction, interactive face to face masterclass style demonstration, opportunity for pupils to practice on mannequins the psychomotor skills involved, including CPR, whilst being observed and a plenary. Pre and post-course questionnaires and focus groups were carried out among pupils and foundation doctors. Results: Results identified a significant improvement in trainee healthcare professionals' perceived leadership skills and pupils' knowledge and confidence of first aid skills. A statistically significant correlation was noted between schools in more deprived regions and increased pupil aspirations to: 1) incorporate 20 minutes of exercise daily and 2) apply for NHS careers. Conclusion s: #HealthinSchools establishes healthcare professionals as leaders of effective first-aid teaching in UK secondary schools with potential benefits for widening participation to NHS careers and promoting healthy behaviour changes to reduce cardio-respiratory disease morbidity.